The Importance of Tabbayyun in Countering Hoax Information in the Digital Era - Muhammad Ikhlas Bin Rosele Lubis; Aura Ajrina Dalimunthe (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
The rapid advancement of information technology and digital communication has significantly transformed the way people access and disseminate information. While digital platforms facilitate fast and widespread information exchange, they have also accelerated the proliferation of hoaxes and misinformation, which can mislead the public, create social unrest, and undermine public trust. In this context, the Islamic principle of tabayyun (verification) offers a relevant ethical framework for addressing the challenges posed by the digital information era. This study aims to examine the importance of tabayyun as a strategy for preventing the spread of hoaxes and promoting responsible digital communication. The research employs a normative juridical approach using descriptive-analytical methods. Data were collected through library research by examining primary sources, including the Qur'an and Hadith, as well as secondary sources such as books, scientific journals, and other relevant literature. The findings indicate that the implementation of tabayyun encourages individuals to verify information before accepting or disseminating it, thereby reducing the spread of misinformation. The study also reveals that digital literacy plays a significant role in strengthening the effectiveness of tabayyun, as individuals with higher levels of digital literacy are more capable of identifying unreliable sources, recognizing misleading content, and critically evaluating information. Furthermore, social influences, technological developments, and the rapid circulation of information present additional challenges to practicing verification consistently. The study concludes that tabayyun is not merely a religious obligation but also an essential digital literacy competency that integrates ethical values with critical thinking skills. Strengthening public awareness through education, digital literacy programs, and collaboration among government institutions, educational organizations, religious leaders, and digital platforms is essential for fostering a healthy, responsible, and trustworthy digital information ecosystem while minimizing the harmful impacts of hoaxes in contemporary society.